2018
DOI: 10.1016/j.neurobiolaging.2018.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Stable olfactory sensory neuron in vivo physiology during normal aging

Abstract: Normal aging is associated with a number of smell impairments that are paralleled by age-dependent changes in the peripheral olfactory system, including decreases in olfactory sensory neurons (OSNs) and in the regenerative capacity of the epithelium. Thus, an age-dependent degradation of sensory input to the brain is one proposed mechanism for the loss of olfactory function in older populations. Here, we tested this hypothesis by performing in vivo optical neurophysiology in 6-, 12-, 18-, and 24-month-old mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…The spatiotemporal blood flow response characteristics and the current and frequency dependence of prompt vasodilation of the olfactory bulb were the same as those previously observed in adult rats [ 17 ]. This is consistent with research by Kass et al [ 25 ] who demonstrated that odor-evoked synaptic output from the olfactory sensory neurons to the olfactory bulb glomeruli is relatively stable in anesthetized mice throughout normal aging, from 6 to 24 months old.…”
Section: Discussionsupporting
confidence: 92%
“…The spatiotemporal blood flow response characteristics and the current and frequency dependence of prompt vasodilation of the olfactory bulb were the same as those previously observed in adult rats [ 17 ]. This is consistent with research by Kass et al [ 25 ] who demonstrated that odor-evoked synaptic output from the olfactory sensory neurons to the olfactory bulb glomeruli is relatively stable in anesthetized mice throughout normal aging, from 6 to 24 months old.…”
Section: Discussionsupporting
confidence: 92%
“…We suggest that among others, hormonal changes could worsen performance aged female opossums in olfactory-guided test. Another paper has shown that responses in OB glomeruli neurons, recorded as neurotransmitter release to different odor applications, did not change in 6–24 month old mice 25 . However, they do not exclude that olfactory impairment during aging may occur in other olfactory brain structures.…”
Section: Discussionmentioning
confidence: 98%
“…This scenario suggests an aged-related parsimonious decay of the VNO that matches the reported effect of natural aging in other olfactory areas like the OB. Several studies have shown that despite the reduced regeneration rate of olfactory sensory neurons (OSNs), OB alterations involving a reduced number of synaptic contacts (Richard et al, 2010), expression defects of odorant receptor genes (Lee et al, 2009; Khan et al, 2013) and changes in the OSNs dynamic range (Kass et al, 2018) are of late occurrence and just becoming obvious in 2-year-old mice. Although the olfactory system may undergo age-related changes from middle age (Mobley et al, 2014), functional deficits during natural aging might exhibit a late onset, suggesting compensatory mechanisms to preserve the processing of olfactory cues like social information relevant for the survival of aged animals (Tobiansky et al, 2012; Tikhonova et al, 2015).…”
Section: Discussionmentioning
confidence: 99%